Impact of the COVID-19 pandemic on imaging case volumes in King Abdullah University Hospitals (KAUH) - Gharaibeh, Maha; El-Obeid, Eyhab; Khasawneh, Ruba; Karrar, Musaab; Salman, Mohamed; Farah, Ahmad; Ahmmed, Sammah; Al-Omari, Mamoon; Elheis, Mwaffaq; Abualigah, Laith (Frontiers in Medicine, 2023)
Objective COVID-19 has an increased burden on the delivery of services because the measures taken by the governments forced hospitals to cancel most of their elective procedures and led to the shutting down of outpatient clinics. This study aimed to evaluate the impact COVID-19 pandemic on the volume of radiology exams based on patient service locations and imaging modality in the North of Jordan. Methods The imaging case volumes that were performed at the King Abdullah University Hospital (KAUH), Jordan, from 1 January 2020 to 8 May 2020, were retrospectively collected and compared to those from 1 January 2019 to 28 May 2019, to determine the impact of the pandemic of COVID-19 on the volume of radiological examinations. The 2020 study period was chosen to cover the peak of COVID-19 cases and to record the effects on imaging case volumes. Results A total of 46,194 imaging case volumes were performed at our tertiary center in 2020 compared to 65,441 imaging cases in 2019. Overall, the imaging case volume in 2020 decreased by 29.4% relative to the same period in 2019. The imaging case volumes decreased for all imaging modalities relative to 2019. The number of nuclear images showed the highest decline (41.0%) in 2020, followed by the number of ultrasounds (33.2%). Interventional radiology was the least affected imaging modality by this decline, with about a 22.9% decline. Conclusion The number of imaging case volumes decreased significantly during the COVID-19 pandemic and its associated lockdown. The outpatient service location was the most affected by this decline. Effective strategies must be adopted to avoid the aforementioned effect on the healthcare system in future pandemics.